POPULISM OR THE BROKEN PROMISES OF DEMOCRACY. CONCEPTS, CAUSES AND SOLUTIONS - AVRAM, Răzvan-Samir (Studia Universitatis Babes-Bolyai Studia Europaea, 2020)
Europe's response to the consequences of the Two World Wars was the need for joint association in a European project. Later on, the communist revolutions have sparked hopes on the European continent in creating a much-dreamed prosperity. One by one, the Eastern European Countries have joined the European project, the last country being Croatia in 2013. Time has passed, but not all problems seem to be resolved, on the contrary, we could say, extremism is on the rise, intolerance of migrants and foreigners it’s a topic on any internal debate. And s as if it weren't enough, Brexit, in conjunction with the rise in the voting intentions for the populist leaders like Marine Le Pen with The National Front in France, Matteo Salvini with Lega Nord in Italy and Nigel Farage with UKIP and later on with Reform Part. This Article aims to provide some clarifications in relation with the conceptual nature of populism, in order to define the concept and identifying and analyzing the main key messages within the populist speech, and also to identify why such messages have success, using as a starting point the idea that populism is only the result of stagnation of the current political class, as well as of the shortcomings of the democratic system.